Inclusiveness and livelihood empowerment in community Forestry projects: the case of SADA afforestation project in Northern Ghana - Osman, Sulley (KNUST, 2025)
A thesis submitted to the School of Graduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirements for the award of degree of Master of Philosophy in Natural Resources and Environmental Governance